Penerapan Higiene dan Sanitasi Lingkungan pada Pasien Diare Balita di Puskesmas Surabaya - Anindita Rehana; Rebekah Juniati Setiabudi; Sulistiawati Sulistiawati; Manik Retno Wahyunitisari (Sarana Ilmu Indonesia (salnesia), 2021)
Surabaya has the most cases of diarrhea in East Java, with the highest detection targets in Gading Health Center (2346 cases) and Mojo Health Center, with diarrhea cases handled by 1322 cases. This study aimed to describe hygiene and environmental sanitation in under-five diarrhea patients in the working area of Surabaya Health Center. This study used a survey method, descriptive approach, interviews, and questionnaires in October 2019-March 2020. The results showed 62,2% of under-fives ‘drinking water sources were ineligible, 86,5% of mothers’ handwashing behavior were ineligible, 67,6% of the use of serving hoods were ineligible, 100% of food ripeness level were eligible, 59,5% of the distance between well and septic tank were eligible, 100% of latrines were eligible, 89,2% of sewerages were ineligible, and 83,8% of waste disposal facilities were ineligible. This research concluded that drinking water sources, handwashing behavior, serving hoods, sewerages, and waste disposal facilities were ineligible. The problems can be solved by consuming branded gallons of water / well water or refillable water that is boiled before consumption, improving how to wash hands with soap and running water, covering food using a serving hood, use the cover to close the sewerage, and throwing the trash into the temporary shelter (TPS) as much as two times a week or less than 3x24 hours.